The Effectiveness of the Zahra Computer Entrepreneurship Skills Education Training Program for Course and Training Institutions on Improving and Developing the Quality of Human Resources for Training Participants in West Lombok Regency in 2024 - Mayanah, Dewi; Maryam, St.; Handayani, Tuti (Westscience Press, 2025)
This study aims to determine the effectiveness of the Zahra Computer Course and Training Institute's Entrepreneurial Skills Education training program on improving and developing the quality of human resources of trainees in West Lombok Regency in 2024. The type of research used is descriptive quantitative. The population in this study were Entrepreneurial Skills Education (PKW) trainees in 2021-2024 and a sample of 20 entrepreneurial skills education (PKW) trainees in 2024 was taken. The research instrument used a questionnaire which was then analyzed using the chi-square test. The results of this study indicate that the significance value (0.000 < 0,50 so that the hypothesis is accepted. So the entrepreneurial skills education training program is very effective and influental in improving and developing the quality of human resources of trainees in West Lombok district in 2024.